Regulation of signaling pathways by Ampelopsin (Dihydromyricetin) in different cancers: exploring the highways and byways less travelled - Fayyaz, Sundas; Qureshi, Muhammad Zahid; Alhewairini, Saleh S; Avnioglu, Seda; Attar, Rukset; Sabitaliyevich, Uteuliyev Yerzhan; Buha, Aleksandra; Salahuddin, Hina; Adylova, Aima; Tahir, Fatima; Pawlak-Adamska, Edyta (Cellular and Molecular Biology, 2019)
Ampelopsin or Dihydromyricetin is gradually emerging as a high-quality natural product because of its ability to modulate wide-ranging signaling pathways. Ampelopsin (Dihydromyricetin) has been reported to effectively modulate growth factor receptor (VEGFR2 and PDGFRÎ²) mediated signaling,  TRAIL/TRAIL-R pathway, JAK/STAT and mTOR-driven signaling in different cancers. Ampelopsin (Dihydromyricetin) has also been shown to exert inhibitory effects on the versatile regulators which trigger EMT (Epithelial-to-Mesenchymal Transition). Findings obtained from in-vitro studies are encouraging and there is a need to comprehensively analyze how Ampelopsin (Dihydromyricetin) inhibits tumor growth in different cancer models. Better knowledge of efficacy of Ampelopsin (Dihydromyricetin) in tumor bearing mice will be helpful in maximizing its translational potential.